Insights into the Structural Determinants Required for High Affinity Binding of Chiral Cyclopropane-Containing Ligands to α4β2-Nicotinic Acetylcholine Receptors; An Integrated Approach to Behaviorally Active Nicotinic Ligands - Zhang, Han-Kun (2012)
Structure-based drug design can potentially accelerate the development of new therapeutics. In this study, a co-crystal structure of the acetylcholine binding protein (AChBP) from Capitella teleta (Ct) in complex with a cyclopropane-containing, selective α4β2-nicotinic acetylcholine receptor (nAChR) partial agonist (compound 5) was acquired. The structural determinants required for ligand binding obtained from this AChBP X-ray structure were used to refine our previous model of the human α4β2-nAChR, thus possibly providing a better understanding of the structure of the human receptor. In order to validate the potential application of the structure of the Ct-AChBP in the engineering of new α4β2-nAChR ligands, homology modeling methods, combined with in silico ADME calculations, were used to design analogs of compound 5. The most promising compound 12, exhibited an improved metabolic stability in comparison to the parent compound 5 while retaining favorable pharmacological parameters together with appropriate behavioral endpoints in the rodent studies.